Evaluating a semi‐nested PCR to support histopathology reports of fungal rhinosinusitis in formalin‐fixed paraffin‐embedded tissue samples. Issue 2 (8th January 2022) - Ashraf, Mohammad Javad; Kord, Mohammad; Morovati, Hamid; Ansari, Saham; Shekarkhar, Golsa; Badali, Hamid; Pakshir, Kayvan; Shamsizadeh, Forough; Khademi, Bijan; Shishegar, Mahmood; Ahmadikia, Kazem; Zomorodian, Kamiar
Abstract: Background: Fungal rhinosinusitis (FRS) encompasses a various spectrum of diseases. Histopathology is the "reference method" for diagnosing FRS, but it cannot determine the genus and species. Moreover, in more than 50% of the histopathologically proven cases, the culture elicited no reliable results. This study was an attempt to evaluate the diagnostic efficiency of semi‐nested polymerase chain reaction (PCR) from formalin‐fixed paraffin‐embedded (FFPE) functional endoscopic sinus surgery (FESS) in FRS patients. Methods: One hundred ten specimens were subjected to DNA extraction and histopathology examination. The amplification of the β‐globin gene by conventional PCR was used to confirm the quality of extracted DNA. The semi‐nested PCR was performed using ITS1, ITS2, and ITS4 primers during two steps. Sequencing the internal transcribed spacer region (ITS1‐5.8S‐ITS2) to identify causative agents was performed on PCR products. Results: Sixty‐four out of 110 samples were positive by histopathology evidence, of which 56 samples (87.5%) were positive by PCR. Out of 46 negative samples by histopathological methods, five samples (10.9%) yielded positive results by PCR. Sensitivity, specificity, positive predictive value, and negative predictive value of the semi‐nested PCR method were reported 87.5%, 89.2%, 92.7%, and 85.2%, respectively. The kappa factor between PCR and histopathological methods was 0.76, indicating substantial agreements between these two tests. Conclusion: Due to the acceptable sensitivity and specificity of the present method, it might be used to diagnose fungal sinusitis infections along with microscopic techniques. This method is recommended to confirm the diagnose of suspected fungal sinusitis with negative histopathology results. Abstract : Following clinical susception, for the fungal rhinosinusitis (FRS), the samples were collected from the rhino‐nasal cavity of 110 patients and were stained by hematoxylin and eosin (H&E), periodic acid‐Schiff (PAS) stains. For the molecular assay, 110 specimens were subjected to DNA extraction and histopathology examination. The amplification of the β‐globin gene by conventional PCR was used to confirm the quality of extracted DNA. The semi‐nested PCR was performed using ITS1, ITS2, and ITS4 primers during two steps. Sequencing the internal transcribed spacer region (ITS1‐5.8S‐ITS2) to identify causative agents was performed on PCR products. Sixty‐four out of 110 samples were positive by histopathology evidence, of which 56 samples (87.5%) were positive by PCR. Out of 46 negative samples by histopathological methods, five samples (10.9%) yielded positive results by PCR. Sensitivity, specificity, positive predictive value, and negative predictive value of the semi‐nested PCR method were reported 87.5%, 89.2%, 92.7%, and 85.2%, respectively. The kappa factor between PCR and histopathological methods was 0.76, indicating substantial agreements between these two tests.